Short Communication: Agro-morphological diversity among four tomato cultivars in western Burundi - FREDERIC NGEZAHAYO; JEAN CLAUDE NGENDAKURIYO; EMMANUEL BIZINDAVYI; CYRILLE MBONIHANKUYE (Society for Indonesian Biodiversity, 2019)
Ngezahayo F, Ngendakuriyo Jc, Bizindavyi E, Mbonihankuye C. 2019. Short Communication: Agro-morphological diversity among four tomato cultivars in western Burundi. Biodiversitas 20: 436-441. Since crop cultivars represent a reservoir of genetic diversity; essential are the understanding and the utilization of genetic variation in tomato accessions for improving the crop. The objective of the present study was to characterize 4 tomato cultivars from the western Burundi by means of 8 agro-morphological traits that could be exploited for tomato crop improvement. Tanya and P20 cultivars showed the lowest plant height but the highest flower number, fruit number and yield per cultivar. This was corroborated by a significant negative correlation between plant height and flower number, fruit number and yield per cultivar in overall results. On the other hand, Floradel and Tengerou97 cultivars have the highest stem circumference and leaf number. Cluster analysis also showed almost four clusters corresponding to one cluster for each cultivar, though Tengerou97 and Floradel tend to be grouped together. Finally, principal component analysis showed that all the eight agro-morphological traits participated in grouping tomato cultivars; particularly flower number, fruit number, plant height, and yield per cultivar. The first three principal component axes accounted for 92.465% of total variation observed among tomato cultivars. Thus, the four cultivars should all be exploited in tomato breeding and improvement programs.